Differences Among Cowpea Rhizobia in Tolerance to High Temperature and Desiccation in Soil - Osa-Afiana, L. O. (1982)
Strains of cowpea rhizobia grew in mannitol-amended, nonsterile soil at 29 to 35°C but not at 40°C. Little decline in numbers of these bacteria occurred in dry, nonsterile soil incubated at 42°C for 7 days. Strains of cowpea rhizobia differed widely in their tolerances to drying at 30°C in nonsterile and sterile soil, and from less than 1 to 50% of the bacteria were still viable after 11 days. No relation was evident between tolerance to desiccation and the degree of aridity of the site from which the bacteria were isolated or their growth rates in culture, but strains not producing extracellular polysaccharide were often more tolerant than those producing extracellular polysaccharide. It is suggested that desiccation-tolerant rhizobia be used for the production of legume inoculants.